The results of endoscopic thyroidectomy via breast-axillary appoach for nodular thyroid goiter at Hue central Hospital - Hiep, Pham Nhu; Dung, Nguyen Viet; Tung, Nguyen Dinh; Phuc, Nguyen Van; Hong, Le Kim; An, Hoang Nguyen Hoai; Hoa, Chau Thi (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.